THE LEVELS OF TNF-Α IN GINGIVAL CREVICULAR FLUID (GCF) OF OSING TRIBE WOMEN WITH OCCLUSAL DISHARMONY - Suhartini Suhartini; Banun Kusumawardani (UPT Penerbitan Universitas Jember)
The Osing tribal region is demographically adjacentto the island of Java, Madura and Bali. The proximityof this demographic regions affects multiple systemsof their organization, culture, and arts. The Osing’sfamilial and societal patterns are similar to the otherJavanese tribes, including housing, food, lifestyle andhealth. Osing tribe is frequently compared toBalinese culture, such as traditional clothing,wedding dresses, and others [1]. One of the culturesassociated with the teeth is Pangur or asa i.e.reducing/flattening the occlusal surfaces of the teethespecially for Osing bride women. In addition, thereis also a tradition of Osing women called Nginang orbetel chewing [2]. This situation may lead to animbalance of dental occlusion and disruption of thenormal flora in the oral cavity alleging effect on oralhealthDental and oral health can be achieved if there is arelationship of harmony and balance between theorgans and tissues in the oral cavity. This is becausethe oral cavity is an integral stomatognatic complexsystem.Stomatognatic system is unitary organ that hasmutual-related functions. These organs include jawbones, temporo mandibular joint (TMJ), teeth, andother supporting structures e.g. masticationmuscles, facial muscles, head and neck. Thisstomatognatic system plays an active role in theprocess of mastication. In normal conditions, itoccurs a harmonious relationship of all componentsof the masticatory system i.e. teeth, muscles, TMJ,lips, cheeks, palate, tongue and salivary secretion[3]. The conditions of normal tooth anatomy andwell-structured on curved teeth will put bothcondyle joints at the center of the articular disc. Thissituation will create an effective mastication process[4].Abnormal condition of tooth structure will causemalocclusion [3]. Occlusion is an interocclusalrelation (intercups) between the teeth of each jaw inaccordance with the position and movement of themandible [5]. Occlusion pathological state is knownas occlusal disharmony. Occlusal disharmony can becaused by several factors such as the loss of teeth,caries, attrition, tooth anomalies, bruxism, and thehabit of chewing on one side [6].Occlusal disharmony is suspected to causeinflammation in periodontal tissues. Periodontaltissue disease is one of the dental and oral diseasethat most commonly occurs. Periodontal diseasescan be caused by bacteria or mechanical theoverloads. The overloads can be caused by theocclusal disharmony. Thus, occlusal disharmony issuspected to cause inflammation in the periodontaltissues. Abnormal oocclusion condition in thisocclusion disharmony leads into occlusal traumawhich will increase the load received by theperiodontal tissue [7]. If this condition is persistent,it will cause periodontal tissue inflammation.Inflammation undergoing locally to the periodontaltissues will induce the immune system to increasethe activity of the inflammatory cytokine secretion,one of which is TNF-α (tumor necrosis factor-alpha).TNF-α will play a role in activating osteoclasts, whichcan result in the destruction of the alveolar bone [8].This inflammatory cytokines can be found in gingivalcrevicular fluid (GCF), which are inflammatoryexudates collected in the gingival sulcus [9].TNF-α is a cytokine that plays a role in theoccurrence of periodontal disease through itsactivities, which triggers proliferation, differentiationand activity of osteoclasts resulting in boneresorption, and inducing production of proteinase inthe cells of the mesenchyme that is responsible inbond tissue destruction. In patients withperiodontitis it occurs increased levels of TNF-α,which will be decreased after periodontal treatment.Based on the description above, it is necessary toknow the levels of TNF-α in GCF Osing women as anindicator of periodontal tissue inflammation due toocclusion disharmony. It is important for preventionand treatment of abnormalities of occlusiondisharmony that will improve oral health and qualityof life, especially in the Osing community in Kemirenvillage, Glagah District, Banyuwangi Regency.